2015
DOI: 10.1007/s13277-015-3171-2
|View full text |Cite
|
Sign up to set email alerts
|

Loss of angiotensin-converting enzyme 2 promotes growth of gallbladder cancer

Abstract: The aim of this study is to investigate the role of angiotensin-converting enzyme 2 (ACE2) in gallbladder cancer (GBC) and the therapeutic potential of angiotensin receptor blocker in GBC. Human gallbladder epithelial cells (HGBEC) together with GBC cells and tissue samples were used. In vitro studies were carried out to investigate the role of ACE2 in GBC cells. ACE2 levels were studied in in vivo GBC mouse models subject to ARB treatment. ACE2 level was decreased in GBC cells compared with that in normal gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
3
31
0
1
Order By: Relevance
“…Our previous studies showed that the ACE2 overexpression inhibited cell growth and VEGF production in vivo (11,12). A recent study also showed that ACE2 suppressed tumor growth in gallbladder cancer (22). In the present study, we found that ACE2 overexpression inhibited the growth of A549-DDP tumor cells in vivo.…”
Section: Discussionsupporting
confidence: 78%
“…Our previous studies showed that the ACE2 overexpression inhibited cell growth and VEGF production in vivo (11,12). A recent study also showed that ACE2 suppressed tumor growth in gallbladder cancer (22). In the present study, we found that ACE2 overexpression inhibited the growth of A549-DDP tumor cells in vivo.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, increased serum ACE2 activity has been reported in healthy individuals (Zong et al, 2015). Moreover, researchers have suggested that decreased ACE2 activity may reflect the presence of cancer associated with diabetes (Pedersen et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…The ACE2/Ang-(1–7)/MasR axis, which represents a newly discovered component of the RAS, has been shown to be up-regulated or down-regulated in different cancers. Yu et al (2016) suggested that ACE2 expression is decreased in breast cancer, NSCLC (Feng et al, 2010), hepatocellular carcinoma (Ye et al, 2015), and pancreatic cancer (Zhou et al, 2009), and Zong et al (2015) reported that ACE2 levels are lower in gallbladder cancer cells than in normal gallbladder cells. Ang-(1–7) is generated primarily from Ang I or AngII via enzymatic cleavage; in recent studies, ACE2 has been identified as the main enzyme that generates Ang-(1–7), whereas ACE has been shown to be responsible for cleaving Ang-(1–7) to produce Ang-(1–5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary tumor site epithelial cells transform into mesenchymal cells through EMT, invading the basement membrane and transferring via blood vessels to form distant secondary tumor sites through MET ( 20 ). Microcircumstances have been considered important in tumor metastasis in previous years, and local RAS, which is expressed in the matrix, may be involved ( 21 ).…”
Section: Discussionmentioning
confidence: 99%